2017
DOI: 10.1139/cjm-2016-0652
|View full text |Cite
|
Sign up to set email alerts
|

Response of microbial communities to roxarsone under different culture conditions

Abstract: Roxarsone is a feed additive widely used in the broiler and swine industries that has the potential to contaminate the environment, mainly via the use of poultry manure as fertilizer, which results in release of inorganic arsenic to the soil and water. This study was conducted to investigate roxarsone degradation and the response of the microbial community under different culture conditions using high-throughput sequencing technology. Poultry litter was incubated for 288 h in the presence of roxarsone under li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…nov. strain OhILAs is capable of transforming ROX (Fisher et al, 2008). In previous studies, Alkaliphilus was shown to be closely correlated with the presence of arsenic and ROX (Liu, Zhang, Li, & Fei, 2017b), which aligns with our own results…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…nov. strain OhILAs is capable of transforming ROX (Fisher et al, 2008). In previous studies, Alkaliphilus was shown to be closely correlated with the presence of arsenic and ROX (Liu, Zhang, Li, & Fei, 2017b), which aligns with our own results…”
Section: Discussionsupporting
confidence: 92%
“…nov. strain OhILAs is capable of transforming ROX (Fisher et al, ). In previous studies, Alkaliphilus was shown to be closely correlated with the presence of arsenic and ROX (Liu, Zhang, Li, & Fei, ), which aligns with our own results showing Alkaliphilus to be the predominant genus of the bacterial community that degraded ROX. However, to our knowledge, we are the first to report the relationship between Proteiniclasticum and arsenic, although further studies are needed to reveal the function of Proteiniclasticum in arsenic transformation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A nationwide survey of animal feeds conducted in 2012 found that the feed products from 34 manufacturers did not meet the safety requirements, and around half of them contained arsenic exceeding the allowable limit . The inorganic arsenic might also result from degradation of ROX in the feeds during storage and handling, as a variety of microbes are capable of degrading ROX, although the actual contribution of this deserves further investigation.…”
Section: Resultsmentioning
confidence: 99%